A case of cutaneous leishmaniasis successfully treated with oral terbinafine in Kenya - Mawenzi, Ramadhan L. (International Journal of Research in Dermatology, 2018)
Leishmaniasis is a tropical disease of the skin and the reticuloendethelial system caused by a parasite of the genus- Leishmania. The disease poses significant psychosocial and public health burdens in endemic areas. Its treatment poses significant challenges considering that new treatment modalities are currently unavailable. The out-dated and toxic antimonial compounds remain the standard treatment. Nevertheless, these agents are mostly unavailable and reports of resistance to these compounds are increasing. Various drugs have therefore been used off label to treat cutaneous leishmaniasis. Terbinafine, an allylamine designed for treatment of fungal infections has been used off label in the treatment cutaneous leishmaniasis in Middle East and India. However, its potential has not been fully exploited in Kenya. This case is reported of a thirteen year old boy, a resident of a leishmaniasis endemic region in Kenya who presented with a symptomless, well demarcated plaque embedded with crusts and papules on his right cheek. Fine needle aspiration cytology revealed leishmania donovani bodies confirming a diagnosis of cutaneous leishmaniasis. He was treated with oral terbinafine 250mg daily for two consecutive months together with topical application of a combination of 10% Chrotamiton + 2% Sulphur cream applied for three consecutive months. A significant improvement evidenced by substantial flattening of the lesion, conspicuous digital image changes and general clinical improvement was noted after 3 months of follow up. This observation endorses oral terbinafine, as an efficacious management of uncomplicated cutaneous leishmaniasis. To limit scarring, an appropriate topical application can be added to oral terbinafine.